2014
DOI: 10.1128/aem.02834-13
|View full text |Cite
|
Sign up to set email alerts
|

Development and Bias Assessment of a Method for Targeted Metagenomic Sequencing of Marine Cyanobacteria

Abstract: Prochlorococcus and Synechococcus are the most abundant photosynthetic organisms in oligotrophic waters and responsible for a significant percentage of the earth's primary production. Here we developed a method for metagenomic sequencing of sorted Prochlorococcus and Synechococcus populations using a transposon-based library preparation technique. First, we observed that the cell lysis technique and associated amount of input DNA had an important role in determining the DNA library quality. Second, we found th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 38 publications
2
14
0
Order By: Relevance
“…1) showed the best amplification of fish DNA in reactions using this amount (see below). This is also consistent with other studies using 2 ng of DNA per 20-25 µl PCR reaction, although amplification can be observed at much lower concentrations (Andrade et al 2012;Jin et al, 2012;Bernal-Martínez et al, 2013;Batmalle et al, 2014;Okeke et al, 2014) To assess the presence and distribution of the inhibitor various PCR-based experiments were designed. All PCR reactions were developed on 1.0-1.7% agarose gels stained with ethidium bromide and the intensity of the bands obtained was observed under UV light in an ImageQuant 300 (General Electric) gel imaging system.…”
Section: Reviewing Manuscriptsupporting
confidence: 86%
“…1) showed the best amplification of fish DNA in reactions using this amount (see below). This is also consistent with other studies using 2 ng of DNA per 20-25 µl PCR reaction, although amplification can be observed at much lower concentrations (Andrade et al 2012;Jin et al, 2012;Bernal-Martínez et al, 2013;Batmalle et al, 2014;Okeke et al, 2014) To assess the presence and distribution of the inhibitor various PCR-based experiments were designed. All PCR reactions were developed on 1.0-1.7% agarose gels stained with ethidium bromide and the intensity of the bands obtained was observed under UV light in an ImageQuant 300 (General Electric) gel imaging system.…”
Section: Reviewing Manuscriptsupporting
confidence: 86%
“…Data are from Martiny et al (2009a). cells from regions with low nutrient concentrations contain a suite of genes for the uptake of nitrogen or phosphorus compounds, but those genes are generally absent in regions with elevated nutrient availability (Martiny et al 2009a,b). This pattern has been observed in Prochlorococcus and Synechococcus as well as multiple heterotrophic bacteria and thus may be a general pattern for marine bacteria (Batmalle et al 2014;Martiny et al 2009a,b;Newton et al 2010); by contrast, this pattern has not been detected in eukaryotic phytoplankton.…”
Section: Figurementioning
confidence: 89%
“…A variant of metagenomics utilizes flow cytometry-based cell sorting to target specific populations (Batmalle et al 2014, Palenik et al 2009, Zehr et al 2008. However, owing to practical limitations in the number of cells sorted, this approach leads to vanishingly small amounts of the DNA.…”
Section: Genomic Diversitymentioning
confidence: 99%
See 1 more Smart Citation
“…Initially, Prochlorococcus was considered unable to use nitrate (NO3), because the original cultured isolates could not use it (Moore et al ). Nevertheless, more recent studies have demonstrated genomic (Martiny et al ; Batmalle et al ; Berube et al ) and indirect physiological (Casey et al ) evidence of NO3 assimilation, in both cultured Prochlorococcus and natural assemblages of Prochlorococcus . Analyzing the genomes of different strains of Prochlorococcus , Berube et al () showed that the genomic configuration of the genes related to the NO3 assimilation differed among Prochlorococcus strains.…”
mentioning
confidence: 99%